Individual and developmental differences in the relationship of preferences and theory of mind - Kristina Leipold; Nora C. Vetter; Marcus Dittrich; Marco Lehmann-Waffenschmidt; Matthias Kliegel (Center for Economic Studies and ifo Institute (CESifo), 2012)
Theory of mind and individual preferences are important determinants in social decision making. The current study examined in a large sample whether being a cooperative preference type is related with better theory of mind skills. Furthermore, by testing adolescents and adults, we examined the impact of age on this relation. Theory of mind is measured in a Public Goods Game. Results indicate that the cooperative type predicted other players. preference types more accurately in the first round of the Public Goods Game. Regarding age differences, cooperative adults estimated the behavior of players of the same type better than cooperative adolescents. Adolescents show lower cooperation levels and a slower adaption of behavior than adults indicating ongoing development of theory of mind in adolescence.
Keywords: C91; D03; D83; H42; 330; theory of mind; social preferences; cooperative behavior; public goods game; Persönlichkeitspsychologie; Soziale Wohlfahrtsfunktion; Entscheidung; Kooperation; Jugendliche; Erwachsene; Öffentliches Gut; Spieltheorie; Theorie